International Handbook of Leadership for Learning
XV, 1357 p.
Keywords: The International Handbook of Leadership for Learning brings together chapters by distinguished authors from thirty-one countries in nine different regions of the world. The handbook contains nine sections that provide regional overviews; a consideration of theoretical and contextual aspects; system and policy approaches that promote leadership for learning with a focus on educating school leaders for learning and the role of the leader in supporting learning. It also considers the challenge of educating current leaders for this new perspective, and how leaders themselves can develop leadership for learning in others and in their organisations, especially in diverse contexts and situations. The final chapter considers what we now know about leadership for learning and looks at ways this might be further improved in the future. The book provides the reader with an understanding of the rich contextual nature of learning in schools and the role of school leaders and leadership development in promoting this. It concludes that the preposition ‘for’ between the two readily known and understood terms of ‘leadership’ and ‘learning’ changes everything as it foregrounds learning and complexifies, rather than simplifies, what that word may mean. Whereas common terms such as ‘instructional leadership’ reduce learning to ‘outcomes’, leadership for learning embraces a much wider, developmental view of learning.